Ilusão concreta: a função estruturante do fetichismo na sustentação ideológica e material da sociedade capitalista, segundo Karl Marx - Lima, Gerson Lucas Padilha de (2022)
The central objective of this thesis is to present the presuppositions and structuring determinations of fetishism - concrete illusion - in supporting the category system of bourgeois political economy, in such a way as to make possible an immanent critique of the same, from the thought of Karl Marx. In this sense, this investigation intends to show the social function that fetishism plays in the ideological and material legitimation concerning the dynamics of capital, and, also, highlight the implications/consequences of this for the revolutionary praxis, which aims to overcome capital. To thematize, answer these questions, we show how fetishism is present throughout the formative theoretical course of Marx's work, even if sometimes implicitly. Simultaneously, we evidence that fetishism permeates all fields of production and reproduction of social life in capitalism. We demonstrate that, although this hypothesis can be proven more explicitly during the Marxian argumentation in Capital, his theoretical and conceptual intuition runs through the entirety of his work in a certain way. To accomplish this task, initially, we carried out a discussion regarding the general idea of fetishism and how it transited and developed in Marx's work; later, we show the development of the idea of fetishism through the explicitness of the contradictions inherent to the commodity (the value form) that appears as something ineliminable to the reproduction of capital, because it is inherent to the elementary cell of wealth in capitalist society; in the third argumentative movement, we show the implications of fetishism for the legitimation of capitalist exploitation through the formation of surplus value, and, through free time (which presents itself as a counterfactual to the socially necessary working time for the production of bourgeois wealth) it establishes itself as a possible immanent form of overcoming fetishism. Fetishism is established as the inverted way in which the thought of political economy and the experience of individuals in general apprehend the contradictory, inverted reality of the social praxis in which they are woven and recognized as social relations in the logic of bourgeois society. In the fetishist conception of reality, the products of human ingenuity appear endowed with a life of their own, autonomous power, regardless of its actual achievement, thus functioning as a form of naturalization, of ideological and concrete legitimation of capitalist society. In this way, the revolutionary act is basically a struggle that aims to overcome the fetishistic character, its presuppositions and its consequences for all instances of the bourgeois order, towards the realm of freedom where the establishment of equality is a necessary condition for the exercise of different human capabilities. Unlike the bourgeois society that is guided by formal/abstract equality, an emancipated society is established by the validity of freedom and concrete equality, where each individual will work for the community based on their specific potential and receive from society a set of wealth corresponding to its integral needs and deficiencies in becoming.